A Genetic Screen To Assess Dopamine Receptor (DopR1) Dependent Sleep Regulation in Drosophila - Yiqin Jiang; Elise Pitmon; Jack Berry; Fred W. Wolf; Zach McKenzie; Tim J. Lebestky (G3: Genes, Genomes, Genetics, 2016)
Sleep is an essential behavioral state of rest that is regulated by homeostatic drives to ensure a balance of sleep and activity, as well as independent arousal mechanisms in the central brain. Dopamine has been identified as a critical regulator of both sleep behavior and arousal. Here, we present results of a genetic screen that selectively restored the Dopamine Receptor (DopR/DopR1/dumb) to specific neuroanatomical regions of the adult Drosophila brain to assess requirements for DopR in sleep behavior. We have identified subsets of the mushroom body that utilizes DopR in daytime sleep regulation. These data are supported by multiple examples of spatially restricted genetic rescue data in discrete circuits of the mushroom body, as well as immunohistochemistry that corroborates the localization of DopR protein within mushroom body circuits. Independent loss of function data using an inducible RNAi construct in the same specific circuits also supports a requirement for DopR in daytime sleep. Additional circuit activation of discrete DopR+ mushroom body neurons also suggests roles for these subpopulations in sleep behavior. These conclusions support a new separable function for DopR in daytime sleep regulation within the mushroom body. This daytime regulation is independent of the known role of DopR in nighttime sleep, which is regulated within the Fan-Shaped Body (FSB). This study provides new neuroanatomical loci for exploration of dopaminergic sleep functions in Drosophila, and expands our understanding of sleep regulation during the day vs. night.